2021
DOI: 10.1182/bloodadvances.2020002709
|View full text |Cite
|
Sign up to set email alerts
|

Restoring RUNX1 deficiency in RUNX1 familial platelet disorder by inhibiting its degradation

Abstract: RUNX1 familial platelet disorder (RUNX1-FPD) is an autosomal dominant disorder caused by a monoallelic mutation of RUNX1, initially resulting in approximately half-normal RUNX1 activity. Clinical features include thrombocytopenia, platelet functional defects, and a predisposition to leukemia. RUNX1 is rapidly degraded through the ubiquitin-proteasome pathway. Moreover, it may autoregulate its expression. A predicted kinetic property of autoregulatory circuits is that transient perturbations of steady-state lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Research on music therapy began in the United States in the early 20th century, with music therapy being used early on for patients with significant physical and mental impairments and gradually expanding after World War II to include treatment for children and adults with special needs affected by intellectual, physical health, mental health, and participation in social activities (such as soldiers in World War II) [6]. Some American researchers have described music therapy as a systematic intervention process in which the music therapist interacts with the patient in different types of musical experiences to achieve therapeutic goals.…”
Section: Related Workmentioning
confidence: 99%
“…Research on music therapy began in the United States in the early 20th century, with music therapy being used early on for patients with significant physical and mental impairments and gradually expanding after World War II to include treatment for children and adults with special needs affected by intellectual, physical health, mental health, and participation in social activities (such as soldiers in World War II) [6]. Some American researchers have described music therapy as a systematic intervention process in which the music therapist interacts with the patient in different types of musical experiences to achieve therapeutic goals.…”
Section: Related Workmentioning
confidence: 99%
“…17 NF-E2 and RUNX1 co-occupy cis elements in megakaryocytes for critical activity of genes in thrombopoiesis. 18 It is not known whether RUNX1 deficiency potentiates stress thrombopoiesis, whether stress thrombopoiesis overcomes RUNX1-FPD-related thrombocytopenia, or whether certain cytotoxic drugs enhance the activity or the abundance of the wild-type RUNX1 protein, similar to proteosome inhibitors, 19 temporarily correcting the thrombocytopenia.…”
Section: Resultsmentioning
confidence: 99%
“…This task requires a clear understanding of the mechanism of why this predisposition exists and how transformation takes place. Krutein et al [123] recently suggested inhibition of RUNX1 degradation as a potential therapy, which they found to be partially effective in an iPSC model containing RUNX1, with a splicing defect resulting in a frameshift and early termination. However, this study also did not determine whether this mutation produced a protein-any protein produced would be truncated without the transactivation domain [123].…”
Section: Discussionmentioning
confidence: 99%
“…Krutein et al [123] recently suggested inhibition of RUNX1 degradation as a potential therapy, which they found to be partially effective in an iPSC model containing RUNX1, with a splicing defect resulting in a frameshift and early termination. However, this study also did not determine whether this mutation produced a protein-any protein produced would be truncated without the transactivation domain [123]. Similarly, overexpression of wild-type RUNX1 partially rescues erythroid and megakaryocyte differentiation defects caused by point mutation in the RHD [124].…”
Section: Discussionmentioning
confidence: 99%